Aerial Separation and Receiver Arrangements on Identifying Lung Syndromes Using the Artificial Neural Network. (23rd August 2022) - Manoharan, Hariprasath; Rambola, Radha Krishna; Kshirsagar, Pravin R.; Chakrabarti, Prasun; Alqahtani, Jarallah; Naveed, Quadri Noorulhasan; Islam, Saiful; Mekuriyaw, Walelign Dinku
Abstract : Lung disease is one of the most harmful diseases in traditional days and is the same nowadays. Early detection is one of the most crucial ways to prevent a human from developing these types of diseases. Many researchers are involved in finding various techniques for predicting the accuracy of the diseases. On the basis of the machine learning algorithm, it was not possible to predict the better accuracy when compared to the deep learning technique; this work has proposed enhanced artificial neural network approaches for the accuracy of lung diseases. Here, the discrete Fourier transform and the Burg auto-regression techniques are used for extracting the computed tomography (CT) scan images, and feature reduction takes place by using principle component analysis (PCA). This proposed work has used the 120 subjective datasets from public landmarks with and without lung diseases. The given dataset is trained by using an enhanced artificial neural network (ANN). The preprocessing techniques are handled by using a Gaussian filter; thus, our proposed approach provides enhanced classification accuracy. Finally, our proposed method is compared with the existing machine learning approach based on its accuracy.